2005
DOI: 10.1093/wber/lhi003
|View full text |Cite
|
Sign up to set email alerts
|

Can We Discern the Effect of Globalization on Income Distribution? Evidence from Household Surveys

Abstract: New data derived directly from household surveys are used to examine the effects of globalization on income distribution in poor and rich countries. The article looks at the impact of openness (proxied by the ratio of trade to GDP) and of direct foreign investment on relative income shares across the entire income distribution. It finds strong evidence that at low average income levels, the income share of the poor is smaller in countries that are more open to trade. As national income levels rise, the incomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
0
27

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 38 publications
11
130
0
27
Order By: Relevance
“…30 From the mid-1980s until 2007, the gradual reduction of inflationary trends in the industrialized world was referred to as the "Great Moderation" thanks to the reduction in the volatility of GDP growth in Australia, Canada, the USA, the UK, Germany, Japan, France and Italy (Summers 2005). 31 For other approaches that examined business cycle fluctuations and monetary policy regimes, see Bergman et al (1998);Milanovic (2005); and Piketty and Saez (2006). of the importance of the common factor grouping all of the economies (i.e., a global factor) with respect to business cycle dynamics.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…30 From the mid-1980s until 2007, the gradual reduction of inflationary trends in the industrialized world was referred to as the "Great Moderation" thanks to the reduction in the volatility of GDP growth in Australia, Canada, the USA, the UK, Germany, Japan, France and Italy (Summers 2005). 31 For other approaches that examined business cycle fluctuations and monetary policy regimes, see Bergman et al (1998);Milanovic (2005); and Piketty and Saez (2006). of the importance of the common factor grouping all of the economies (i.e., a global factor) with respect to business cycle dynamics.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The same opinion is expressed by Easterlin (2001) who concluded that aspects of income and financial situation as well as physical and psychological needs are the key indicators of the rural community's quality of life in several developing countries. In the meantime, Diener and Lucas (2000), Ravallion (2001) and Milanovic (2002) in their studies found that communities who live in the rural areas are more inclined to choose objective well-being such as material aspects and basic facilities as the main indicator in determining their quality of life.…”
Section: Results Of the Study And Discussionmentioning
confidence: 99%
“…In their OLS analysis of cross-section and time-series data they find no significant results for a correlation between FDI and inequality measured by the Gini coefficient. Milanovic [2003], assessing the influence of globalization on income deciles derived directly from household surveys, also cannot find any significant influence of FDI on income distribution. 4 In a brief review of the existing literature Nunnenkamp and Thiele [(2004), pp.…”
Section: Previous Researchmentioning
confidence: 97%